Network RTK performance analysis: a case study in Latvia - Dobelis, Didzis; Zvirgzds, Jānis (Geodesy and Cartography, 2016)
Nowadays the RTK (Real Time Kinematic) method for positioning is used in daily life by different consumers for many purposes. Several different RTK correction techniques are used, starting from single site to network approaches. The GNSS market is filled with receivers from different manufacturers and different capabilities. In this paper we assess the stability of the reference station network transmitted RTK correction. Two different surveying class GNSS receivers in combination with four varied RTK correction techniques under diverse observation conditions are analyzed. This study has been conducted in Latvia, where state wide permanent GNSS reference station network has been maintained since year 2005.